Elementary Aspects of the Political Histories from the Global South - Banerjee, Prathama (Theory in Forms, 2021)
Prathama Banerjee moves beyond postcolonial and decolonial critiques of European political philosophy to rethink modern conceptions of "the political" from the perspective of Indian and Bengali practices and philosophies from the late nineteenth and early twentieth centuries.